Survey of cat owners on features of, and preventative measures for, feline scratching of inappropriate objects: a pilot study. Issue 10 (October 2018) - Moesta, Alexandra; Keys, Deborah; Crowell-Davis, Sharon
Objectives: The objective of this study was to collect preliminary data on relevant features and preventative measures of feline inappropriate scratching. Preliminary data could then be used to inform future randomized controlled studies. Methods: A paper questionnaire was distributed to 140 cat-owning clients of a small animal practice. The response rate was 82.9%. Questions related to features of inappropriate and designated items scratched, frequency of the behavior and how owners attempted to modify the behavior. The frequency of scratching was ranked and analyzed with repeated-measures models for differences between features of items. The effectiveness of techniques to modify scratching was analyzed with Student's t -tests comparing frequencies of scratching between cats of survey participants who did and did not use specific techniques. Results: Scratching of inappropriate items was reported for 83.9% of cats. Most cats (81.5%) scratched chairs or other furniture and 64.1% scratched carpet. The frequency of scratching inappropriate items was significantly influenced by type and material of the items scratched, with furniture and carpet, and fabric and carpet, respectively, being scratched most often. Most cats (76.1%) had a designated scratching item. The frequency of scratching designated items was significantly influenced by type, with cats using scratching posts and other items more often than scratch pads. Owners used a variety of punishment- and reward-based techniques to stop inappropriate scratching and encourage scratching of designated items; only one technique was found to have a significant effect, with the frequency of scratching designated items being significantly lower in cats that were placed near the item. Conclusions and relevance: Furniture covered with fabric was an object frequently scratched. Fabric should be further investigated as a potential material to encourage desired scratching behavior. Scratch pads appeared less desired than scratching posts. Punishment was a common strategy to deter scratching but did not appear to influence the frequency of scratching.